The Social Thought of Zygmunt Bauman - Tester, K. author. aut Link
VIII, 202 p.
Keywords: Zygmunt Bauman is one of the most important contemporary social thinkers. He has changed the way we think about the Holocaust, postmodernity and globalisation. This is the first book to discuss all of Bauman's work, from the first essays in post-Stalinist Poland, through to his participation in 1960s Marxist revisionism, and up to the work for which he is well known in the West. Bauman's work is put into its social and historical context, and it is shown why Bauman matters.